Evaluation of Superior Semicircular Canal Morphology and Its Relationship with Glenoid Fossa Roof Thickness Using Cone Beam Computed Tomography - Bahare Davvaz; Mahvash Hasani; Abdolaziz Haghnegahdar (Radiology Research and Practice)
Purpose. This study aimed to evaluate the bone thickness of the superior semicircular canal (SSC) roof and its relationship with the roof thickness of the glenoid fossa (RGF). Methods. The cone beam computed tomography (CBCT) images of 280 patients (560 temporal regions) were surveyed. The lowest thickness of the SSC roof was measured and categorized based on the radiological patterns of the Cisneros et al. classification. The thickness of GF and the presence of dehiscence in this part were determined, as well. The relationship between the thickness of the GF roof and the bone thickness covering the SSC was also assessed. Results. The mean thickness of the SSC roof was 0.93 ± 0.48 mm, with no significant difference among different age groups and genders (p>0.05). However, superior semicircular canal dehiscence (SSCD) was more prevalent among females over 45 years old. Similarly, the individuals with the dehiscence of the GF roof had a 12.93-fold higher chance of SSCD development. Conclusions. The results indicated that the thickness of the bone overlying the SSC was significantly related to the roof thickness of the GF. However, an increase in age resulted in no significant change in the bone thickness of the SSC roof. Gender also had no role in changing the thickness of the bone overlying the SSC. Considering the decrease in the thickness of the SSC roof among females over 45 years of age, menopause may be responsible for this occurrence as well as for the increase in the prevalence of SSCD.